New sinusoidal oscillator configurations using operational transresistance amplifier. (20th March 2019) - Komanapalli, Gurumurthy; Pandey, Rajeshwari; Pandey, Neeta
Summary: The objective of this brief is to introduce four new structures of electronically tunable sinusoidal oscillators (SOs) designed using operational transresistance amplifier (OTRA). Each of the proposed SO consists of forward path derived from a generic structure along with one/two OTRA‐based resistive gain stages or differentiator in its feedback path. All the proposed SOs enjoy independent tuning of the frequency of oscillation (FO) through resistors without affecting the condition of oscillation (CO). Further, all topologies are found to exhibit low f o sensitivities at all frequencies with respect to circuit parameters, and the second topology is capable of achieving very low frequencies (VLFs) using less RC component spread and provides linear tuning too. The fourth circuit provides quadrature output. The proposed SOs have been successfully implemented and verified in 180‐nm CMOS technology node using ADE (analog design environment) tool Cadence Virtuoso. Both prelayout and postlayout simulation results have been included. To assess the oscillator prefabrication performances, Monte Carlo and process‐voltage‐temperature (PVT) analyses have been performed. The total harmonic distortion (THD) is observed to be less than 3.5%. Abstract : This paper presents OTRA‐based four electronically tunable sinusoidal oscillators (SO). Each of the proposed SO consists of forward path derived from a generic structure along with resistive gain stage(s)/differentiator in feedback path. The frequency of oscillation (FO) of the proposed SOs can be tuned independently without affecting the condition of oscillation (CO), and all topologies exhibit low FO sensitivities with respect to circuit parameters.